RESPON STRES SEKUNDER IKAN NILA (Oreochromis niloticus) TERHADAP DOSIS HIDROGEN PEROKSIDA (H2O2) YANG BERBEDA SELAMA MASA TRANSPORTASI - Viola Nur Maghribfa; Putri Desi Wulan Sari; Lailatul Lutfiyah (Airlangga University, 2023)
Fish transportation is a crucial step in maintaining fish quality during the shipping process from one region to another. The closed-wet system, which is commonly used for fish transportation, has several obstacles in the form of fish stress and mortality. Stressed fish generate primary, secondary, and tertiary stress responses. The purpose of this study is to assess the secondary stress response of tilapia during transportation by giving different doses of hydrogen peroxide. 3% hydrogen peroxide applied to water resulting in three different doses i.e. 0.3 ml.L-1 , 0.1 ml.L-1 , 0.08 ml.L-1 and without hydrogen peroxide used as control groups. Data was obtained by measuring blood glucose levels and the ventilation rate of tilapia. The results showed an alteration in blood glucose levels and ventilation rate of tilapia during transportation. Treatment with 0.1 ml.L-1 hydrogen peroxide gave the lowest glucose levels during 10 hours of transportation. Changes in ventilation rate of tilapia were observed in the treatment with 0.1 ml.L-1 of hydrogen peroxide which indicated miled stress conditions. It can be concluded that the optimal dose of hydrogen peroxide in the transportation process is 0.1 ml.L-1 of hydrogen peroxide.